The Relationship Between The Tutor'S Learning Method With The Activity Of The Learners Package C In Pkbm Pratama, Pancung Soal District, Pesisir Selatan - Wisri Febriani; Jamaris Jamaris (Universitas Negeri Padang, 2022)
This research was motivated by the activeness of learning residents in Package C at PKBM Pratama, Pancung Problem District, Peisir Selatan Regency, using the lecture method, discussion method, demonstration method, question and answer method, and practice methods in learning. This study aims to see an overview of the application of the learning methods used by tutors during PBM, to see the activeness of learning residents in participating in the PBM Package C process and the relationship between tutor learning methods and the activities of residents studying Package C at PKBM Pratama.This type of research is quantitative with a correlational approach. The population in this study were all learning residents who took part in the Package C Pratama program in 2020 as many as 112 people. While the sampling technique using the Simple Random Sampling technique, as many as 50% of the 112 people, namely 56 people. The data collection technique used a questionnaire distributed to the residents studying Package C, while the data analysis technique used the Percentage and Product Moment formulas.The results of this study indicate that the learning methods used by tutors are less varied so that the activeness of the learning community is categorized as low, and there is a significant relationship between the tutor's learning method and the activeness of the learning community in package C. The suggestion in this study is that tutors should use varied learning so that the activeness of the citizens more increased.Keywords: Learning Methods, Active Learning, Quantitative, Correlation